KADAR ELEKTROLIT DAN GULA DARAH PADA PASIEN KEJANG DEMAM DI RSUD ULIN BANJARMASIN - Helmy, Muhammad Dzaky; Hidayah, Nurul; Huldani, Huldani; Hartoyo, Edi; Illiandri, Oski (Universitas Lambung Mangkurat, 2023)
The most common neurological disease in children is febrile seizures, preceded by a rise in body temperature of 38°C or more. In general, electrolyte and blood sugar checks are still often requested in the treatment of febrile seizures. According to the consensus on the management of febrile seizures, this examination cannot be carried out routinely, only to find out the source of the infection. This study aims to determine electrolyte and blood sugar levels in patients with febrile seizures and patients with fever without seizures. This study was conducted using a Cross Sectional Study with 30 cases each, for febrile seizures and fever without seizures. The sampling technique was carried out by purposive sampling method. Data was taken from medical records at Ulin Banjarmsin General Hospital, namely patient data, electrolyte levels (Na+ and K+), and blood sugar (RBG). The data was taken at the Ulin Hospital in Banjarmasin. Data analysis used chi-square (R2) to see the relationship between electrolyte levels and blood sugar in patients with febrile convulsions and patients with fever without seizures. The results of data analysis on sodium levels (p=0.754) and potassium levels (p=0.317) showed no significant difference. The results of data analysis for blood sugar levels (p=0.114) also found no significant difference. The results of this study concluded that in the incidence of febrile seizures and fever without seizures, there were no differences in electrolyte and blood sugar levels.